Polyvinyl chloride microplastics induce growth inhibition and oxidative stress in Cyprinus carpio var. larvae - Xia, Xiaohua; Sun, Menghan; Zhou, Miao; Chang, Zhongjie; Li, Li (The Science of the total environment, 2020)
The occurrence and accumulation of microplastics in wildlife and humans have become a serious global scale concern over the last decade. To evaluate the potential toxic effects of PVC (polyvinyl chloride) microplastics in freshwater fish larvae, we conducted chronic 30-day and 60-day dietary exposure using Cyprinus carpio var. larvae. We exposed the larvae to four treatments with different microplastic concentrations (10%, 20%, and 30%) using food rationed diets, in conjunction with a non-plastic control. The results indicated that microplastics significantly inhibited weight gain and growth under all PVC treatments, compared to the control group. SOD (superoxide dismutase) and CAT (catalase) activities were analyzed, and an inverse relationship between them was observed. The activities of GPx (glutathione peroxidase) initially ascended and then descended with increased PVC concentrations following 30 days of exposure. A dose dependent downtrend was observed after 60 days of exposure. Malondialdehyde (MDA) levels were significantly reduced upon exposure to different concentrations of microplastics in various tissues. Altered antioxidant-related gene expression was observed in the livers of larvae exposed to the PVC microplastics. The transcription of CYP1A and GSTa initially increased, and then decreased under higher microplastics concentrations following 30 days of exposure. Furthermore, histological studies revealed cytoplasmic vacuolation in the liver under exposure to 20% and 30% microplastics. This investigation provided basic toxicological data toward elucidating and quantifying the impacts of PVC microplastics on freshwater organisms. [Display omitted] •PVC microplastics inhibited weight gain and body length growth of carp larvae.•Antioxidant activities were altered following PVC microplastics exposure.•PVC microplastics influenced the expression levels of CYP1A, GSTpi, and GSTa.•Histological changes occurred in the livers of fish exposed to PVC microplastics.